PENGARUH PENERAPAN BAHAN AJAR FISIKA BERMUATAN NILAI NILAI KARAKTER PADA KONSEP LISTRIK DINAMIS DALAM PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA KELAS X SMA N 4 PADANG - Anggreini Anggreini (Universitas Negeri Padang, 2013)
Student learning outcomes for the physics lesson still has not appropriate with expected. One of the cause is of applying teaching materials of physics still not integrating character values. The aim of this research is to see the influence of implementation teaching materials of physics which is integrating character values on dynamic electricity concept in cooperative learning type STAD towards students learning outcome grade X SMA N 4 Padang. Type of research is quasi experimental research. The population in this study were all students of grade X SMA N 4 Padang listed in the 2nd half of the school year 2012/2013. Sample of research is selected by purposive sampling technique. Data analysis using the t test on the real level of 0.05 obtained results that there are the influence of implementation teaching materials of physics which is integrating character values on dynamic electricity concept in cooperative learning type STAD towards students learning outcome grade X SMA N 4 Padang. Keywords: Teaching Materials, Character Values, Cooperative Learning, Learning Outcomes